In–plane shear properties of basalt–carbon/epoxy hybrid composite laminates: In–plane Schereigenschaften von Basalt-Kohlenstoff/Epoxy-Hybrid-Verbundlaminaten - Mengal, A.N. (Wiley-VCH Verlag, 2017)
In this work, the in-plane shear properties of basalt-carbon/epoxy hybrid composite laminates is investigated. The composite laminates were fabricated using the hand layup method. Six symmetrical lamination stacking sequences (02C/±45B/0BS, 02C/0B/±45BS, 02C/±452BS, 0B/±45B/02CS, ±45B/0B/02CS, ±452B/02CS) with eight layers of unidirectional 0 ° and biaxial ±45 ° were selected for the current study. One eight-layered unidirectional 0o fiber layup of pure carbon fiber and one eight-layered unidirectional 0o fiber layup of pure basalt fiber were used as a reference. The in-plane shear strength of the composite laminates were determined experimentally according to the ASTM D7078 standard. The hybridization of basalt fiber and carbon fiber showed significant improvement in the in-plane shear strength and modulus of rigidity. The failure of the composite laminates was examined using the ASTM D7078 standard failure codes. Hybrid composite laminates C2 and B2, i. e. for 02C/±45B/0BS and 0B/±45B/02CS, respectively had the highest in-plane shear strength while pure carbon C1 and pure basalt B1 with 08C and 08B, respectively had the lowest shear strength. © 2017 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim